2020
DOI: 10.1111/nuf.12536
|View full text |Cite
|
Sign up to set email alerts
|

Exploring nurse suicide by firearms: A mixed‐method longitudinal (2003–2017) analysis of death investigations

Abstract: Background: Previously it was noted that firearm use by nurses in suicide was changing. The Center for Disease Control and Prevention suicide dataset contains investigation narratives that no researcher has analyzed and may provide context to inform suicide prevention.Objective: Explore firearm deaths in nurse suicide. Second, test topic modeling techniques to analyze investigation narratives.Methods/Statistical Analysis: Mixed-method retrospective analysis of 739 nurse versus 94,838 nonnurse suicides. Odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…40 This means of suicide is consistent with the general population where death by firearms is much more common than death by poisoning. 6,40,41 Similar to nursing but different from physicians, benzodiazepines, antidepressants, and opioids were the most common substances found in the pharmacist suicides. 6,8 Although caution must be exercised when trying to understand the characteristics of suicide in this small sample, it is worthwhile to examine the significant findings in this study.…”
Section: Discussionsupporting
confidence: 84%
“…40 This means of suicide is consistent with the general population where death by firearms is much more common than death by poisoning. 6,40,41 Similar to nursing but different from physicians, benzodiazepines, antidepressants, and opioids were the most common substances found in the pharmacist suicides. 6,8 Although caution must be exercised when trying to understand the characteristics of suicide in this small sample, it is worthwhile to examine the significant findings in this study.…”
Section: Discussionsupporting
confidence: 84%
“…While the CDC provides detailed Users’ Manuals for the NVDRS (Centers for Disease Control and Prevention 2020 , 2021 , 2022b ), there is a general lack of concrete guidance on how to reconcile incongruencies and integrate text narratives with the abstractor-coded variables. This review found that researchers who utilize the narratives as a means of case finding or case confirming often privilege the content within the qualitative data in classifying or categorizing cases and incident circumstances when coded variables were found to be insufficient (Davidson et al 2021a ; Lohman et al 2021 ; Yau and Paschall 2018 ; Wertz et al 2020 ). However, few studies reported information on missingness or incompleteness of these texts, much less how such data issues were addressed in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Standard NLP preprocessing steps were followed: investigation narratives with five or fewer characters were removed, yielding the 204 CME and 188 LE narratives for analysis. Remaining NLP preprocessing and analysis steps have been described previously (Davidson et al, 2021) and may be found in Appendix A.…”
Section: Methodsmentioning
confidence: 99%